Nutrition landscape and climate in Vietnam: Identifying climate service entry points - Singh, Pranav; Huynh, Tuyen; Downs, Shauna (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This paper comprises a current state assessment of the nutrition landscape in Vietnam to identify potential climate service entry-points. Through secondary research of global databases, ministry websites and previous studies in this field we mapped a list of nutrition-specific and nutrition-sensitive interventions, stakeholders, and data sources in Vietnam. This was followed by interviews with key stakeholders, which highlighted the major challenges and opportunities for using climate data to inform programs and policies aimed at improving nutritional outcomes within the country. The results indicate there are capacity and coordination challenges amongst government departments and between government and development agencies. The key stakeholders we interviewed are cognizant of the effect of climate on food systems and nutrition. It is possible, therefore, that with an increased awareness at the leadership level necessary systemic changes can be achieved. It is recommended to prioritize the inclusion of climate indicators into the nutrition surveys in particular and policy decisions in general, followed by strengthening the data-sharing (climate data) and coordination mechanisms between departments. Finally, the upcoming National Nutrition Strategy (2021-30) offers a great opportunity to formalize the climate and nutrition linkage, while also highlighting the urgency of the matter.